2014
DOI: 10.1155/2014/419425
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complementary and Alternative Medicine on Subfertile Women with In Vitro Fertilization

Abstract: About 10–15% of couples have difficulty conceiving at some point in their reproductive lives and thus have to seek specialist fertility care. One of the most commonly used treatment options is in vitro fertilization (IVF) and its related expansions. Despite many recent technological advances, the average IVF live birth rate per single initiated cycle is still only 30%. Consequently, there is a need to find new therapies to promote the efficiency of the procedure. Many patients have turned to complementary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Traditional Chinese medicine (TCM), considered gentle and safe, has long been used to treat infertility and miscarriages [ 20 , 21 ]. It has also exhibited effectiveness in improving embryonic implantation rates in IVF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), considered gentle and safe, has long been used to treat infertility and miscarriages [ 20 , 21 ]. It has also exhibited effectiveness in improving embryonic implantation rates in IVF [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to maximize the efficiency of the procedure. Many patients have turned to complementary and alternative medical (CAM) treatments such as acupuncture to increase the success rate of assisted reproductive technology (ART) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Many infertile women have now turned to complementary and alternative medicine as an adjuvant therapy to improve the outcomes when they undergo IVF treatment. 4 Acupuncture, as an effective non-pharmacological therapy, has been chosen by many infertile couples undergoing infertility treatment. 3,[5][6][7][8] It is reported that "fertility problems" is the second most common health condition for which people choose acupuncture treatment in the UK.…”
Section: Introductionmentioning
confidence: 99%